Especies de Carangidae inusuales durante el Niño costero 2017 en el litoral de Pisco, sur del Perú - Donayre-Salazar, Susan (2022)
This work reports the unusual presence of species of the Carangidae family in Pisco province coast (13.5° S), department of Ica, which occurred during the El Niño costero 2017 event. Four species were observed: Caranx caballus, Caranx caninus, Oligoplites saurus y Selene brevoortii were captured with the “cortina agallera” fishing gear. During the El Niño costero 2017 in the study area, temperatures above 26 °C and moderately high salinities (> 35.1 ups) were recorded, conditions would have favored the displacement of these species, frequent in the north of Peru, towards higher latitudes.